Interobserver variability in the assessment of aneurysm occlusion with the WEB aneurysm embolization system. (1st July 2014) - Fiorella, David; Arthur, Adam; Byrne, James; Pierot, Laurent; Molyneux, Andy; Duckwiler, Gary; McCarthy, Thomas; Strother, Charles
Abstract : Objective: The WEB (WEB aneurysm embolization system, Sequent Medical, Aliso Viejo, California, USA) is a self-expanding, nitinol, mesh device designed to achieve aneurysm occlusion after endosaccular deployment. The WEB Occlusion Scale (WOS) is a standardized angiographic assessment scale for reporting aneurysm occlusion achieved with intrasaccular mesh implants. This study was performed to assess the interobserver variability of the WOS. Methods: Seven experienced neurovascular specialists were trained to apply the WOS. These physicians independently reviewed angiographic image sets from 30 patients treated with the WEB under blinded conditions. No additional clinical information was provided. Raters graded each image according to the WOS (complete occlusion, residual neck or residual aneurysm). Final statistics were calculated using the dichotomous outcomes of complete occlusion or incomplete occlusion. The interobserver agreement was measured by the generalized κ statistic. Results: In this series of 30 test case aneurysms, observers rated 12–17 as completely occluded, 3–9 as nearly completely occluded, and 9–11 as demonstrating residual aneurysm filling. Agreement was perfect across all seven observers for the presence or absence of complete occlusion in 22 of 30 cases. Overall, interobserver agreement was substantial (κ statistic 0.779 with a 95% CI of 0.700 to 0.857). Conclusions: The WOS allows a consistent means of reporting angiographic occlusion for aneurysms treated with the WEB device.